2020
DOI: 10.3389/fonc.2020.562574
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Pathway Regulators Predict Clinical Prognostic Risk and Affect the Tumor Immune Microenvironment in Lung Adenocarcinoma

Abstract: The ceramide pathway is strongly associated with the regulation of tumor proliferation, differentiation, senescence, and apoptosis. This study aimed to explore the gene signatures, prognostic value, and immune-related effects of ceramide-regulated genes in lung adenocarcinoma (LUAD). Methods: Public datasets of LUAD from The Cancer Genome Atlas and Gene Expression Omnibus were selected. Consensus clustering was adopted to classify LUAD patients, and a least absolute shrinkage and selection operator (LASSO) reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Whether the LUAD prognostic model we established in this study has an advantage, we also answer in this paper. By comparison, the prognostic power of our model was better than the eight studies ( 51 58 ) from the most recent year.…”
Section: Discussionmentioning
confidence: 73%
“…Whether the LUAD prognostic model we established in this study has an advantage, we also answer in this paper. By comparison, the prognostic power of our model was better than the eight studies ( 51 58 ) from the most recent year.…”
Section: Discussionmentioning
confidence: 73%
“…However, the mechanisms by which BAK1 mediates pyroptosis and leads to LUAD remain elusive. CYCS , as a mitochondrial protein that participates in the regulation of cell death, was reported to be an oncogene in LUAD 35 . Previous research has demonstrated that serum CYCS levels are correlated with disease progression and a poor prognosis in NSCLC 36 , which is consistent with our current results.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we used UALCAN to analyze the relationship between mRNA expression of BIRC5 and CDO1 and clinical staging of AJCC-TNM in breast cancer patients. 22 Furthermore, the information on tumor immune estimation was obtained from the TIMER database ( https://cistrome.shinyapps.io/timer/ ) 23 and followed by some relevant literature retrieval. 24 We analyzed the correlation of BIRC5 or CDO1 mRNA levels with infiltrated immune cells and immune markers of various immune cells in breast cancer tissue.…”
Section: Methodsmentioning
confidence: 99%